P669 Adherence to self-administered biologic therapies in inflammatory bowel disease: Experience in a tertiary hospital. (15th January 2020) - Ramos Lopez, L; Ramos Rodríguez, J; De La Barreda, R; Guitierrez, F; Nazco Casariego, G J; Alonso Abreu, I; Carrillo Palau, M; Quintero, E
Abstract: Background: Nonadherence to medications is common in patients with inflammatory bowel disease (IBD) and can result in disease complications, therapy escalation, and the need for corticosteroids. The aim of this study was to assess adherence to self-administered (subcutaneous) biologic medications prescribed for IBD and to identify risk factors for biologic nonadherence. Methods: A retrospective cohort study was performed on IBD patients starting and receiving subcutaneous biologic therapies from January 2016 to July 2019. Medical records were retrospectively reviewed and demographic and IBD data were collected. A modified medication possession ratio (mMPR) was calculated for the first 12-month treatment and at the end of follow-up (global-42 months). Nonadherence was defined as mMPR of less than 90%. Multiple regression analysis was performed to assess risk factors associated with non-adherence therapy Results: A total of 154 patients (84M/70F; mean age starting biologic treatment 36 ±14 years; Crohn's disease n = 118/ ulcerative colitis n = 31/ indeterminate colitis n = 5) were included; 121 received Adalimumab (ADA) and 33 were on Ustekinumab (UST); 63% of patients were naive to anti-TNF and 16.9% had received >2 previous biological treatment. Mean time from IBD diagnosis to use of subcutaneous biological agent was 16 ± 10 months. Mean time of subcutaneous agents use was 17.6(SD11.0) and 17.08 (SD6.8)months for ADA and UST, respectively. Global nonadherence ( n = 154) (≤90% mMPR) was 6.6% for all patients receiving subcutaneous treatment and 6.3% for ADA and 6.5% for UST. Nonadherence during first 12-month treatment ( n = 98) was 6.1% for all patients and 2.7 % for ADA and 16% for UST, respectively. In the multivariate analysis, Ustekinumab use was independently associated with higher nonadherence only for first 12-months adherence (OR 6.7, 95% CI 1.1–39.5). Conclusion: Self-administered biologic treatment showed adequate global adherence in our study. Using subcutaneous administration for biologic agents in IBD patients forces us to monitor and control their adherence to ensure the therapeutic benefit.